Predicting the Potential Applicability to Other Technical Fields Through the Linkage Between Backward and Forward Citations - Hirose, Masayuki (Frontiers in Research Metrics and Analytics, 2021)
This article is a modest attempt to shed some light on the question of linkages between backward and forward citations in technical fields posed by Trajtenberg, Henderson and Jaffe (1997). They found interesting similarities and high correlations between equivalent measures looking forward and backward. They implied that “coming from far away in technology space leads far away." Although it is becoming clear that forward citations are a good predictor of important inventions, it is imperative to take quite a wide time window in order to get significant coverage of forward citations, which makes it difficult to count all of the forward citations in early stage. In this article, the author reconsider the possibility of the prediction method using backward citations instead of forward citations as a starting point by re-evaluating the linkage between the two suggested by them. To verify the linkage of such citations, the author proposes a new analysis method which makes it possible to divide a set of patent applications into three categories depending on the degree of proximity to the technical field into which the subject invention was classified. Using such new analysis method, the author creates two hypotheses and tested them for about 14,000 examined patent applications filed in 2008 with Japanese Patent Office. As a result of testing the hypothesis I, the author confirmed that patent applications citing backward citations categorized as the distant technical field are more likely to be cited by forward citations categorized as the distant technical field as compared to the possibilities of the other technical fields. In addition, by testing the hypothesis II, the authors also confirmed that the degree of agreement between the patent classification of backward citations categorized in Distant Fields and that of forward citations categorized in Distant Fields is higher than in the same or neighboring fields. The author believes that the new method further improves the accuracy of the prediction method, which makes it possible to find patent applications for inventions with potential applicability to other technical fields at an early stage without relying on forward citations.